Knowledge, practices and influencing factors defining unhealthy food behavior among adolescents in India: a scoping review - Jena, Susangita; Parida, Jayashree; Panda, Arpita; Behera, Swati Sukalyani; Pradhan, Abinash; Patra, Prasanna Kumar; Pati, Sanghamitra; Kaur, Harpreet; Acharya, Subhendu Kumar (Frontiers in Psychology, 2023)
Unhealthy food behaviors are the major contributing factors to the rising burden of non-communicable diseases (NCDs) among adolescents in India. Knowledge and practices related to unhealthy eating are significant factors influencing adolescents’ food behavior. In this scoping review, we aim to map evidence and identify gaps on knowledge, practices, and the influencing factors associated with unhealthy food behavior among Indian adolescents by examining the existing literature. Arksey and O’Malley’s scoping review framework and the Joanna Briggs Institute Reviewers’ manual were used for this review. After the screening, 33 articles were identified according to the inclusion criteria. Data extraction was performed according to the study objectives, followed by narrative summarization. The studies included a total of 20,566 adolescents. Most studies reported insufficient knowledge about healthy food choices among adolescents. Diet intake patterns among the adolescents showed a lower amount of fruits and vegetables and an increase in fried items, sugar-sweetened beverages, packaged food, and fast food in both sexes, with a broader association with peer influence (21.2%), parental unhealthy food behavior (15.1%), place of residence (6.06%), emotional status (6.06%), and mass media exposure (18.1%). The scoping review highlights the need for targeted interventions aimed at improving the knowledge and practices of Indian adolescents by promoting healthy food choices and sensitizing them about the risk of non-communicable diseases. The analysis of evidence around adolescent dietary behavior in India shows a monotonous, limited, and narrow range in scope, indicating the extended need for research.